TINJAUAN PEMBANGUNAN GEDUNG FAKULTAS PERTANIAN UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Puji Hariyanto; Ishak Ishak; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Development in various sectors in the city of Payakumbuh continues to grow from time to time. In the process of building a building there are several stages that must be done. The most important thing is the resistance of the building structure to the planned load and the resilience of the structure to disasters, and to find out the need for careful planning and proper structural calculations so that the structure can last longer. In this final project the building being reviewed is the Faculty of Agriculture, Muhammadiyah University West Sumatra, Payakumbuh City. The calculation of the structure refers to SNI 2847-2013 for reinforced concrete design, SNI 1726-2012 for design against earthquakes using the 2019 earthquake response spectrum and SNI 2052-2014 and PPIUG 1983 for loading on structures. The calculation of the building structure is reviewed for dead loads, live loads and earthquake loads. The calculations carried out include plate, beam, and column elements. SAP2000v11 application is used to help the calculation of forces in structural elements.Keywords: SAP 2000, SNI 1726-2012, 2019 earthquake response spectrum, SNI 2052-2014,PPIUG 1983